1969
DOI: 10.1037/h0027473
|View full text |Cite
|
Sign up to set email alerts
|

Digital and kinesthetic memory with interpolated information processing.

Abstract: Four experiments were conducted on the effects of interpolated activity on retention of digits and of specific kinesthetic events. Experiment I replicated Posner and Rossman's finding that short-term forgetting of digits is an increasing function of the size of the information-reducing transform in the interpolated task. Experiment II confirmed Posner and Konick's finding that short-term memory for a specific kinesthetic event does not depend on digital information-processing capacity available during the rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
3
1

Year Published

1971
1971
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 10 publications
3
30
3
1
Order By: Relevance
“…Marteniuk's (1973) findings, as well as those of the present study, demonstrate no forgetting under preselected conditions until the interpolation of central processing activity. On the other hand, constrained movements decayed spontaneously over the IS-sec retention interval and, in line with the AE data of Posner (1967) and Williams, Beaver, Spence, and Rundell (1969), showed no further effect of occupying the processing channel. The coupling of these two findings suggests that preselected movements are represented centrally to a greater degree than those of the constrained condition.…”
Section: Discussionsupporting
confidence: 83%
“…Marteniuk's (1973) findings, as well as those of the present study, demonstrate no forgetting under preselected conditions until the interpolation of central processing activity. On the other hand, constrained movements decayed spontaneously over the IS-sec retention interval and, in line with the AE data of Posner (1967) and Williams, Beaver, Spence, and Rundell (1969), showed no further effect of occupying the processing channel. The coupling of these two findings suggests that preselected movements are represented centrally to a greater degree than those of the constrained condition.…”
Section: Discussionsupporting
confidence: 83%
“…The studies of Brooks (1968) and Williams et al (1969) could provide an explanation why the verbal and combination groups in Experiment 2 did not show speed-speci® c interference. According to Williams et al (1969), activities that deal with kinaesthetic memory show interference eþ ects on the recall accuracy of movements and not on the recall of linguistic variables.…”
Section: Discussionmentioning
confidence: 93%
“…According to Williams et al (1969), activities that deal with kinaesthetic memory show interference eþ ects on the recall accuracy of movements and not on the recall of linguistic variables. Brooks (1968) noted a distinction between imagery and verbal processes by showing that pointing responses interfered more with visual imagery, whereas verbal responses interfered more with the verbal recall of sentences.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that disruption of delay behavior is a significant source of retroactive interference in animals and humans (Anderson & Craik, 1974;Kulp, 1967;Moise, 1970;Murdock, 1967;Posner & Konick, 1966;Pylyshyn, 1965;Thompson, Van Hemel, Winston, & Pappas, 1983;Tranberg & Rilling, 1980;Williams, Beaver, Spence, & Rundell, 1969). For example, Moise (1970) found that the matching accuracy of monkeys was directly correlated with the number of responses on a reaction-time task interpolated into the delay intervals.…”
mentioning
confidence: 99%